TreeFTL: An Efficient Workload-Adaptive Algorithm for RAM Buffer Management of NAND Flash-Based Devices - Wang, Chundong; Wong, Weng-Fai (IEEE transactions on computers, 2016)
NAND flash memory is widely used for the secondary storage of computer systems. The flash translation layer (FTL) is the firmware that manages and operates a flash-based storage device. One of the FTL's modules manages the RAM buffer of the flash device. Now this RAM buffer is sufficient to be used for both address mapping and data buffering. As the fastest component of the flash layer interface, effective management of this buffer has a significant impact on the performance of data storage and access. This paper proposes a novel scheme called TreeFTL for this purpose. TreeFTL organizes address translation pages and data storage pages in a tree-like structure in the RAM buffer. The tree enables TreeFTL to adapt to the access behaviors of workloads by dynamically adjusting the partitions for address mapping and data buffering. Furthermore, TreeFTL employs a lightweight mechanism to evict the least-recently-used victim pages when the need arises. Our experiments show that TreeFTL is able to spend 46.6 and 49.0 percent less service time over various workloads than two state-of-the-art algorithms, respectively, for a 64 MB RAM buffer.